2016
DOI: 10.1038/srep31414
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Adiponectin Levels Suppress Perivascular and Aortic Inflammation and Prevent AngII-induced Advanced Abdominal Aortic Aneurysms

Abstract: Abdominal aortic aneurysm (AAA) is a degenerative disease characterized by aortic dilation and rupture leading to sudden death. Currently, no non-surgical treatments are available and novel therapeutic targets are needed to prevent AAA. We investigated whether increasing plasma levels of adiponectin (APN), a pleiotropic adipokine, provides therapeutic benefit to prevent AngII-induced advanced AAA in a well-established preclinical model. In the AngII-infused hyperlipidemic low-density lipoprotein receptor-defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 52 publications
(86 reference statements)
0
17
0
Order By: Relevance
“…Sections were then stained for collagen and elastin as previously described [13]. Sections were studied under light microscopy ZEN 2012 (Zeiss, Jena, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sections were then stained for collagen and elastin as previously described [13]. Sections were studied under light microscopy ZEN 2012 (Zeiss, Jena, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Paraffin-embedded sections (5 μm) from mice aorta were rehydrated in several changes of ethanol and Tissue-Clear ® (Sakura Finetek). Sections were then stained for collagen and elastin as previously described [ 13 ]. Sections were studied under light microscopy ZEN 2012 (Zeiss, Jena, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Light to moderate alcohol consumption has been associated with lower levels of inflammation markers including interleukin-6 (an upstream maker of C-reactive protein or fibrinogen) [20,21], whose receptor is an important pathway for the development of abdominal aortic aneurysm [22]. Furthermore, moderate alcohol consumption reduced platelet aggregation [23] and circulating MMP-2 activity [24], enhanced fibrinolysis [25], and increased adiponectin level [18], all of which contribute to the reduced risk of aortic diseases [26][27][28] . Although the causality cannot be determined from an observational study, our findings could be generalized to middle-aged men of other ethnicities according to these mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Ten eligible rodent studies were identified (19)(20)(21)(22)(23)(24)(25)(26)(27)(28). These studies included a total of 319 rodents in which the effects of leptin, resistin, adiponectin, and PVAT were investigated (19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Detailed information about each study is shown in Table 1.…”
Section: Animal Studies Investigating the Role Of Adipokines Or Pvat mentioning
confidence: 99%